THE RESULTS OF THE ALL-RUSSIAN COMPETITION FOR THE BEST SCIENTIFIC BOOK - Natal’ya A. Lyashchenko; Liliya M. Voitenko; Elita G. Mnatsakanyan (Высшее образование в России, 2016)
The article is devoted to the results of the annual All2Russian competition for the best scientific book in 2013 conducted among university professors and academic staff of research institutions. The annual competition is held on the base of the International Innovative University in Sochi. There have been presented more than 4,000 books in 2014.